Design of Traffic Cone Collector Machine - Bock, Meng Siong; Sia, Chee Kiong (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The traffic cone collecting process may be time-consuming, labor-intensive, and dangerous to workers. Therefore, the "Design of Traffic Cone Collector Machine" project seeks to address the ongoing issues of efficiently managing and collecting traffic cones on roads. The objectives of this project are to investigate the existing traffic cone collecting and storage mechanism, to identify the most efficient traffic cone collecting and storage mechanism and to design a complete traffic cone collector machine. The scopes of the research are analyse the existing traffic cone collector machines, study the types and sizes of traffic cones commonly used in Malaysia, develop a detailed design for the traffic cone collector machine, design an automated traffic cone collecting mechanism, design an automated traffic cone storage mechanism and validate the traffic cone collecting and storage mechanism. The design of the machine is drawn and simulate using Solidwork software. The final design of the machine shows that it can collect the traffic cone at 10s per cone and have a storage capacity of 390 traffic cones.